2002
DOI: 10.1089/088922202317406637
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factorα, Interleukin 2, and Soluble Interleukin 2 Receptor Levels in Human Immunodeficiency Virus Type 1-Infected Individuals Receiving Intermittent Cycles of Interleukin 2

Abstract: HIV-infected individuals with 200-500 CD4(+) T cell/microl were enrolled in a controlled study of three interleukin 2 (IL-2) plus antiretroviral therapy (ART) regimens: (1) continuous intravenous administration of 12 million international units (MIU) of IL-2 followed by subcutaneous high-dose IL-2 (7.5 MIU, twice daily) for 5 days every 8 weeks; (2) high-dose subcutaneous IL-2 for 5 days every 8 weeks; (3) low-dose (3 MIU, twice daily) subcutaneous IL-2 for 5 days every 4 weeks; and (4) ART alone. Serum concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Unadjusted median IL-2 and GM-CSF concentra-tions (Table 3) and adjusted mean concentrations (accounting for lab and lot differences) were lower in HIV ϩ subjects, which is consistent with published reports suggesting defects in production of these two cytokines as a result of HIV infection (6,10,25). In other reports, serum concentrations of IL-2 or GM-CSF were consistently below the level of detection or showed lower median concentrations in HIV ϩ subjects (7,11,14). It is likely, therefore, that the differences detected by the high-sensitivity Linco kit reflect the significantly lower frequency of detectable results in HIV ϩ than HIV Ϫ subjects (for IL-2, 55% versus 78% [P ϭ 0.02]; for GM-CSF, 35% versus 68% [P ϭ 0.007]).…”
Section: Vol 18 2011 Multisite Comparison Of Multiplex Cytokine Asssupporting
confidence: 89%
“…Unadjusted median IL-2 and GM-CSF concentra-tions (Table 3) and adjusted mean concentrations (accounting for lab and lot differences) were lower in HIV ϩ subjects, which is consistent with published reports suggesting defects in production of these two cytokines as a result of HIV infection (6,10,25). In other reports, serum concentrations of IL-2 or GM-CSF were consistently below the level of detection or showed lower median concentrations in HIV ϩ subjects (7,11,14). It is likely, therefore, that the differences detected by the high-sensitivity Linco kit reflect the significantly lower frequency of detectable results in HIV ϩ than HIV Ϫ subjects (for IL-2, 55% versus 78% [P ϭ 0.02]; for GM-CSF, 35% versus 68% [P ϭ 0.007]).…”
Section: Vol 18 2011 Multisite Comparison Of Multiplex Cytokine Asssupporting
confidence: 89%
“…In addition, this study showed that IL‐2 therapy induced the expansion of CD4 + CD25 + T cells, although CD25 expression was not evaluated in CD8 + T cells. Another study reported that IL‐2 therapy of HIV + individuals increased the release of sCD25, an indicator of disease progression 120 …”
Section: Receptor Expression and γC Cytokine Therapeuticsmentioning
confidence: 99%
“…Another study reported that IL-2 therapy of HIV + individuals increased the release of sCD25, an indicator of disease progression. 120 Given that immune deficiency persists despite increased concentrations of plasma IL-7 in HIV infection, higher IL-7 concentrations may be required to restore T-cell homeostasis and overcome such impaired T-cell function. Therefore, clinical trials are underway to assess the use of IL-7 as a therapeutic agent in HIV infection.…”
Section: Receptor Expression and C C Cytokine Therapeuticsmentioning
confidence: 99%
“…Interleukin 2 (IL-2) is a critical cytokine required for T cell activation, proliferation, and function [reviewed in (20, 21)]. However, IL-2 also induces secretion of proinflammatory cytokines like IL-6, IL-1β and tumor necrosis factor alpha (TNF-α) (22–24), and is associated with increased levels of inflammatory markers like C-reactive protein (CRP) and D-dimer in the plasma of HIV-infected subjects, independent of HIV viral load (25). In addition, in vitro activation of peripheral blood mononuclear cells (PBMCs) with IL-2 increases HIV production (26, 27).…”
Section: Introductionmentioning
confidence: 99%